An Evaluation Of Factors Affecting The Choice Of The Different Roofing Materials In Residential Within Kedah State Of Malaysia - Amin, Fatimah Nur Mohammad (Universiti Sains Malaysia, 2022)
The roof of the building is one of the most important structural elements that performs the protective and insulating functions for heat preservation and overheat protection, protection from external adverse factors for all types of precipitation, wind, melt water. There are two parts to a roof, its supporting structure and its outer skin, or uppermost weatherproof layer, which is directly exposed to atmospheric influences. This part of the roof shows great variation dependent upon availability of material, (J. Testa, 2017). The roof also has its own importance, according to Christopher Gorse (2012b) The roof is the very upper part of a building that protects structures and other elements from rain. Water had to be able to run off the structure, therefore it had to be appropriately sloped. However, if designed and built incorrectly, they might be a never-ending source of problems. The definition of a roof is a climax house, which is on top once and serves as the main protector from hot, rainy to the occupants in the house (Library). This study aims to identify the problem of roofing type and material from the perspective of the occupants to identify the suitability of the use of roofing material and type for residential houses. Respondents for this study were occupants of houses either self-built or completed houses from developers. This study uses questionnaire methods distributed on social media are presented in the form of tables and graphs. The results of the study found two the main problem is the problem in terms of the type and material of the roof of the house. While for the maintenance perspective for the roof problem because it is sloppy and not worth it. The suitability of the roofing material can be seen that the use of roofing this type is not very suitable for use in Malaysia due to hot climate factors and rainfall throughout the year simultaneously affecting the structure this type of roof.